31. IMPATIENT EXPERIENCE ON INTERACTION WITH HEALTHCARE STAFF AT HA TINH REHABILITATION HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2025)
Objectives: To describe inpatient experiences and analyze associated factors at Ha Tinh Rehabilitation Hospital in 2023.Method: A cross-sectional study was conducted on 238 inpatients across 5 clinical departments/units. Data were collected using a structured questionnaire based on the consumer assessment of healthcare providers and systems tool and analyzed with SPSS 23.0.Results: Patients highly appreciated the attitude and interaction of doctors, nurses, and technicians, with the percentages of patients having positive experiences being 91.6%, 82.3%, and 79,8%, respectively. Upon hospital admission, patients also had a relatively high positive experience with the interaction of medical staff. However, this rate was quite low among security and parking staff (53%).Conclusions: The study provides practical evidence for hospital leaders to improve service quality and patient experience.
Keywords: Patient experience; doctors; nurses; rehabilitation hospital; service quality.